Mendelian randomization study highlights the role of hematological traits on Type-2 diabetes mellitus in African ancestry individuals - Soremekun, Chisom; Jjingo, Daudi; Kateete, David; Nash, Oyekanmi; Nitsch, Dorothea; Nyirenda, Moffat; Gill, Dipender; Zeggini, Eleftheria; Grallert, Harald; Peters, Annette; Chikowore, Tinashe; Batini, Chiara; et al. (Frontiers in Pharmacology, 2025)
IntroductionObservational studies have identified associations between hematological traits and type-2 diabetes mellitus (T2D). However, it is difficult to infer causal effects due to the potential of confounding. Our study utilizes the Mendelian randomization (MR) approach to address the above limitation and investigate the causal effect of hematological traits such as white blood cell (WBC), platelets (PLT), and red blood cell (RBC) on T2D in individuals of African ancestry.MethodsThe participating cohorts included participants of African ancestry in the Blood Cell consortium and the Million Veteran Program dataset. Using GWAS summary statistics, we applied a univariable and multivariable Two-sample MR to estimate the causal relationship between hematological traits and T2D.ResultsIn the main IVW MR estimates, genetically predicted levels of mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH), and mean corpuscular volume (MCV) were associated with decreased risk of T2D. We also observed a decreased risk of T2D with genetically predicted total WBC count and neutrophil count (NEU), for the WBC traits. The multivariable analysis further supported the direct associations of genetically predicted MCH, MCHC, and MCV levels with a decreased risk of T2D. For the European ancestry, a similar pattern of association was observed for MCH and MCV.DiscussionThese findings indicate that hematological traits may differentially play a role in the development of T2D and be affected by T2D. However, further research is needed to validate and explore the biological pathways and mechanisms involved in these associations.